Analysis of port‐wine birthmark vascular characteristics by location: Utility of optical coherence tomography mapping. Issue 1 (9th December 2021) - Wang, Jordan V.; Mehrabi, Joseph N.; Abrouk, Michael; Pomerantz, Hyemin; Palma, Anton M.; Zachary, Christopher B.; Waibel, Jill S.; Kelly, Kristen M.; Geronemus, Roy G.
Abstract: Introduction: Port‐wine birthmarks (PWBs) are congenital capillary malformations that can be located on any area of the body. Vascular features include vessel size, depth, and density, which can greatly differ between patients, individual lesions, and even sites within the same lesion. Previous studies have determined that the location of PWB lesions has impacted their clinical response to laser treatment. Objective: We utilized dynamic optical coherence tomography (D‐OCT) to measure in vivo vessel diameter, density, and superficial plexus depth in patients of all ages with PWB on various sites of the body. We hypothesized that these vascular characteristics would differ according to body location. Materials and Methods: Patients who had a PWB and presented to clinic at three sites for treatment with the pulsed dye laser (PDL) were enrolled into the study. A D‐OCT scanner was utilized for noninvasive, in vivo imaging of PWB lesions. The depth of the top portion of the superficial vascular plexus was estimated as the depth at which the vessel density reaches 50% of the maximum. Vessel diameter and density were calculated by incorporated software algorithm. Results: A total of 108 patients were enrolled into the study. There was a total of 204 measurements of PWB lesions. Of all patients, 56.5% ( n = 61) reported having a previous treatment with PDL. Of all D ‐OCT scans, 62.3% ( n = 127) were located on the head, 14.2% ( n = 29) the upper extremities, 8.3% ( n = 17) the lower extremities, 7.8% ( n = 16) the trunk, and 7.8% ( n = 15) the neck. All locations were compared for each vascular characteristic. For superficial plexus depth, lesions on the head were significantly shallower than those on the upper extremities (217 vs. 284 µm; p < 0.001) and lower extremities (217 vs. 309 µm; p < 0.001). For vessel diameter, lesions on the head had significantly larger vessels than those on the upper extremities (100 vs. 72 µm; p = 0.001). For vessel density, lesions on the head had significantly denser vessels than those on the trunk (19% vs. 9.6%; p = 0.039) and upper extremities (19% vs. 9.3%; p < 0.001) Conclusions: PWB lesions have distinct vascular characteristics, which can be associated with their body location. This includes superficial vascular plexus depth as well as vessel diameter and density.